Nursing community 2.0: a method to promote online collaborative learning. (13th November 2019) - Arnone, R; Cascio, M I; Parenti, I; Catino, A; Zoda, M L; Botta, V C
Abstract: : This article describes a project seeking to establish an online community of practice involving nurses in Sicily, known as Nursing Community 2.0. The Community has initially involved 585 Sicilian nurses who took part in the residential activities. They had been selected thorough a questionnaire addressed to measure the initial technological competencies. All students - registered on open source LMS (Moodle) - attended DL courses promoted by CEFPAS (Centre for training and Research in Public Health located in Sicily). To promote collaborative Learning, Learning Community provided 4 areas: Forum, to confront and to debate about professional interests moderated by a renowned nurse; Camera Cafè, a virtual "agora" to change opinion without a moderator; The corner of the joke; a Tweetboard; Project work Area, where the Topic has been developed to be presented during the last examination. Indeed, the project was designed to provide nurses with a space for building collaborative relationships, exchanging professional knowledge and practices, developing competencies, shaping organizational policy and reporting Adverse Drug Reactions. The quality of solutions will depend on the professional and on the nature of the competencies to be developed. The impact of a training initiative addressed to an adult public through the technological tool, depends both on the interest for the topic and on the ability of the user to manage own training, to acquire familiarity with network services and technologies and, when it occurs, to be able to autonomously cope with training using technologies useful to get information and knowledge to be used to solve a specific professional problem in time. Qualitative and quantitative analysis of online interactions have been carried out. Results indicate that, thanks to the deployment of suitable technology and expert tutor support, Nursing Community 2.0 has successfully established itself as an environment for generating and exchanging knowledge. Key messages: Collaborative learning depends on the interest for the topic and on the ability of the user to manage learning through technological tools. Nursing Community gives results when learning environment generates debates and interactions.